Flash pyrolysis of kerogens from algal rich oil shales from the Eocene Huadian Formation, NE China - Zhang, Z.; Volkman, J.; Greenwood, Paul; Hu, W.; Qin, J.; Borjigin, T.; Zhai, C.; Liu, W. (Pergamon, 2014)
The hydrocarbon composition of the kerogen fractions of two samples (HD-20 and HD-21) from oil shale layer 4 in the Eocene Huadian Formation, NE China were investigated by analytical flash pyrolysis (650 C/10 s) followed by gas chromatography–mass spectrometry (Py–GC–MS). Organic petrography showed that the two kerogens were almost entirely derived from algal remains but contained very different algal maceral compositions, with 40% of the macerals in HD-20 being of macroalgal origin that were not present in HD-21. Py–GC–MS yielded high concentrations of n-alkanes from both kerogens, but with different molecular weight profiles due to the different algal contributors to the two kerogen samples. The hydrocarbon pyrolysates generated at 650 C from HD-21 in which the green microalga Botryococcus braunii was identified showed a higher proportion of longer chain alkanes and alkenes presumably from cracking of the botryococcus algaenan. We also identified a C40 monoaromatic lycopane derivative, which was absent in the HD-20. The high hydrocarbon potential of both kerogens can be attributed to common microalgal sources, whereas the macroalgae, which is abundant in HD-20, makes only a minor contribution to the hydrocarbon products.